2017
DOI: 10.1038/s41598-017-01985-w
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic system for monitoring temporal variations of hemorheological properties and platelet adhesion in LPS-injected rats

Abstract: Sepsis causes multiple organs failures and eventually death. Changes in blood constituents due to sepsis lead to alterations in hemorheological properties, and cell adhesiveness. In this study, a new microfluidic system is proposed to measure temporal variations in biophysical properties of blood after injecting lipopolysaccharide (LPS) into a rat extracorporeal model under ex vivo condition. To measure blood viscosity, the interfacial line between blood and a reference fluid is formed in a Y-shaped channel. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The experimental results indicated that blood flow stopped shortly within 0.2 s. After clamping the tube, image intensity (< I >) tended to increase immediately. According to previous studies [ 17 , 28 ], blood flow decreased gradually based on the compliance effect of the microfluidic system when a syringe pump was used to control blood flow in a microfluidic channel in the delivery mode. In other words, when the syringe pump was set to zero value of the flow rate (i.e., Q = 0), RBC aggregation did not occur due to transient blood flow in the microfluidic channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results indicated that blood flow stopped shortly within 0.2 s. After clamping the tube, image intensity (< I >) tended to increase immediately. According to previous studies [ 17 , 28 ], blood flow decreased gradually based on the compliance effect of the microfluidic system when a syringe pump was used to control blood flow in a microfluidic channel in the delivery mode. In other words, when the syringe pump was set to zero value of the flow rate (i.e., Q = 0), RBC aggregation did not occur due to transient blood flow in the microfluidic channel.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, when the syringe pump was set to zero value of the flow rate (i.e., Q = 0), RBC aggregation did not occur due to transient blood flow in the microfluidic channel. Thus, RBC aggregation was quantified by using temporal variations in image intensity after an elapse of 20 s [ 28 ] or 60 s [ 17 ]. For this reason, a glass capillary tube [ 2 ] or detour channel [ 14 ] was applied to minimize time delay due to the compliance effect of the microfluidic system.…”
Section: Resultsmentioning
confidence: 99%
“…The previous study has reported that biophysical properties of blood samples (hematocrit (Hct), viscosity, and erythrocyte sedimentation rate (ESR)) are strongly correlated with coronary heart diseases [3]. Thereafter, the biophysical properties of the blood sample have been studied extensively for the effective monitoring of circulatory disorders [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…within a specific value of the interface. As the interface was relocated periodically within a specific range (0.1 < α B < 0.9), two approximate factors (F 1 and F 2 ) with constant values were calculated from Equations (12) and (13).…”
Section: Of 19mentioning
confidence: 99%
“…The viscosity of the blood sample is then quantified by using reverse flow-switching phenomena under a constant blood flow. Additionally, blood viscosity is obtained by monitoring the interface in coflowing streams, while the flow rates of the blood sample and reference fluid remain constant at the same flow rate with two syringe pumps [12,13]. However, because the blood sample includes viscoelasticity (viscosity and elasticity) under a periodic flow condition, it is necessary to quantify the viscoelasticity of the blood sample without a flow regulator (i.e., periodic flow rate).…”
Section: Introductionmentioning
confidence: 99%